The Intragenerational Redistributive Effects of Unfunded Pension Programs - Cubeddu, Luis (IMF Working Papers; Working Paper ;, 1998)
This paper provides a quantitative evaluation of the intracohort redistributive elements of the U.S. social security system in the context of a computable general equilibrium model. It determines how the well-being of individuals that differ by gender, race, and education is affected by the government's social security policy. Differences in life expectancy and labor productivity translate into differences in capital accumulation and labor supply distortions that are responsible for the observed welfare difference between individuals of the same age cohort.